Understanding Behaviour and Space Organization for Sustainable Housing at Pandemic Covid-19 (International Journal of Architecture and Urbanism, 2025)
The surge in COVID-19 cases in mid-2021 across several cities in Indonesia saw a rapid increase, with research confirming that the virus spreads primarily through direct contact, including respiratory droplets from coughing and sneezing. In the context of residential settings, the virus exhibits a high rate of transmission, particularly within family units, making family clusters a significant concern, especially in urban areas. This study examines a family in Tangerang living in a small residential space, focusing on understanding their behavior, the organization of their living spaces, and the home's lighting and ventilation systems. Using a phenomenological approach rooted in qualitative research, this study identifies key factors contributing to the potential spread of COVID-19, including: 1) poor ventilation; 2) inadequate natural lighting; 3) frequent use of shared spaces; and 4) the absence of dedicated isolation areas for infected individuals. These findings provide insight into the typologies of homes that may contribute to family clusters. Based on these case study results, this research proposes recommendations for sustainable housing designs that are better equipped to manage pandemic situations. These recommendations include: 1) incorporating isolated rooms; 2) providing access to private outdoor spaces for sunbathing; and 3) relocating public spaces such as living rooms to areas with better air circulation and natural lighting.